Prevalence and Clinical Impact of Cervical Facet Joint Degeneration on Degenerative Cervical Myelopathy: A Novel Computed Tomography Classification Study - Ai Okamoto; Yasuhiro Takeshima; Shohei Yokoyama; Fumihiko Nishimura; Ichiro Nakagawa; Young-Soo Park; Hiroyuki Nakase (Neurospine, 2022)
Objective To evaluate cervical facet joint degeneration using a newly developed classification, investigate its prevalence and relationship with cervical degenerative spondylolisthesis, and clarify its clinical significance in patients with degenerative cervical myelopathy (DCM). Methods This study included 145 consecutive patients with DCM who underwent surgical treatment. Clinical variables and radiological findings were analyzed. A new 6-grade computed tomography (CT) classification for cervical facet joint degeneration was adapted, and its prevalence was evaluated by categorizing the joints into those at responsible and those at nonresponsible spinal segmental levels. We evaluated the association between rapidly progressive myelopathy and the presence of significant facet joint degeneration or spondylolisthesis at the responsible segmental level. Results Finally, 140 patients with a mean age of 64.1 ± 12.8 years were analyzed. The prevalence of grade 1, 2, 3, 4, 5A, and 5B classification in all facet joints was 72.0%, 9.5%, 10.9%, 4.3%, 2.9%, and 0.4%, respectively. There was a statistically significant difference in the distribution of CT grades between the joints at the responsible and nonresponsible segmental levels (p < 0.001), with a high prevalence of grade 4 or 5B degeneration at the responsible segmental level, reflecting articular irregularity. There was also a statistically significant relationship between rapidly progressive myelopathy and grade 4 or 5B degeneration at the responsible segmental level (p < 0.001), but not between rapidly progressive myelopathy and spondylolisthesis (p = 0.255). Conclusion This novel CT classification for facet joints deserves additional evaluation in patients with DCM. Abnormal findings on the articular surfaces might be related to the progression of myelopathy.